Accuracy of Uric Acid and Cholesterol Levels Examination in Distinguishing Pleural Effusion Fluid Exudates and Transudates - Sutanto, Yusup Subagio (Indonesian Journal of Medicine, 2021)
Background: Light's criteria was reported 25% of misclassification transudates as exudates. This study aimed to analyse the accuracy of examining uric acid levels and pleural fluid uric acid levels, and pleural fluid cholesterol and cholesterol ratios to distinguish the exudates and transudates in pleural effusions.Subjects and Method: This was a cross-sectional study design conducted at Dr. Moewardi Hospital, Surakarta, Central Java, from July to August 2019. The study subjects were 30 pleural effusion patients treated in the pulmonology ward. The dependent variables were pleural fluid exudates and transudates. The independent variables were (1) Uric acid levels in pleural fluid; (2) The ratio of uric acid levels between pleural fluid and serum; (3) Pleural fluid cholesterol levels; and (4) The ratio of cholesterol levels between pleural fluid and serum. The study instruments were Light's criteria and laboratory examination. The diagnosis's accuracy was analysed using sensitivity, specificity, and the area under the ROC (AUC) curve.Results: Pleural fluid cholesterol showed sensitivity and specificity of 86% and 83%, with a cut-off of 32.00 for transudate results. AUC value = 0.82 with p = 0.012. Serum cholesterol showed sensitivity and specificity of 71% and 61%, with a cut-off of 175.50 for transudate results. AUC value = 0.67 with p = 0.194. Pleural fluid uric acid levels showed a sensitivity and specificity of 86% and 87%, with a cut-off of 7.25 for transudate results. AUC value = 0.83 with p = 0.009. Examination of serum uric acid levels showed a sensitivity and specificity of 86% and 70%, with a cut-off of 7.10 for transudate results. AUC value = 0.65 with p = 0.249.Conclusion: Examination of uric acid and pleural fluid cholesterol levels can be used in routine pleural effusion examinations to distinguish exudates and transudates.Keywords: accuracy, uric acid, exudates, cholesterol, transudatesCorrespondence: Yusup Subagio Sutanto. Department of Pulmonology and Respiratory Medicine, Faculty of Medicine Universitas Sebelas Maret, Dr. Moewardi Hospital, Surakarta. Jl. Kolonel Sutarto 132, Jebres, Surakarta 57126, Central Java. Email: dr_yusupsubagio@yahoo.com. Mobile: +62811284165.Indonesian Journal of Medicine (2021), 06(02): 159-167https://doi.org/10.26911/theijmed.2021.06.02.05